2007
DOI: 10.5713/ajas.2007.1272
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sensory Traits and Preferences between Food Co-product Fermented Liquid (FCFL)-fed and Formula-fed Pork Loin

Abstract: Sensory traits and preferences regarding food co-product fermented liquid (FCFL)-fed pork loin were compared with those of formula-fed pork. The FCFL-fed pork was expected to have improved fat meltability. Thirty-nine laboratory panelists took part in a sensory test. The fat meat and the lean meat of FCFL-fed pig were judged more meltable and tender, respectively, than the corresponding meat from the formula-fed pig. These sensory traits agreed closely with the results of a mechanical investigation of fat melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Actually, the ‘Ecofeed’ system developed in Japan does not decrease pork quality (e.g. Sasaki et al . 2007; Ohmori et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Actually, the ‘Ecofeed’ system developed in Japan does not decrease pork quality (e.g. Sasaki et al . 2007; Ohmori et al .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there are several reports about consumer preferences regarding pork produced with food waste or co‐products. For example, Sasaki et al . (2007) presented Japanese panelists' preferences regarding pork fed fermented liquid of food co‐products.…”
Section: Introductionmentioning
confidence: 99%
“…Kang et al (2010) reported that pork quality was affected by the ratio of carbohydrate to fat of fermented diet and Sasaki et al (2007) reported that supplementation of fermented food co-product had affected pork quality. The carcass grade may be affected by values of nutrition or ME in fermented diet.…”
Section: Discussionmentioning
confidence: 99%
“…Fat is the carrier of taste [Sasaki et al 2007], so products from which fat was partially or wholly removed are usually characterised by weaker sensory values compared to their traditional counterparts. Studies by Jaworska [2007] showed that the level of acceptance of low-fat quark cheese among consumers was signifi cantly lower.…”
Section: Discussionmentioning
confidence: 99%